How to cross a marquess - Ashford, Jane (Ashford, Jane. Way to a lord's heart, 2019)
"The Marquess of Chatton and his neighbor Fenella Fairclough have known each other all their lives. They refused to marry each other years ago when their parents demanded it, and they won't concede now - even if circumstances have brought these former enemies much closer than they ever could have anticipated..."--Publisher description.